"Here Being in School Is Worse": How Latinx Teachers Navigate, Recreate, and Instigate Hostile Spaces in the U.S. South. Issue 1 (2nd January 2022) - Monreal, Timothy
Abstract: This qualitative investigation about Latinx K-12 teachers in South Carolina fills a gap in the academic literature because there is a dearth of research examining Latinx teachers' spatial/racial experiences in the U.S. South. Centering an explicitly spatial frame, I map out three broad relations to what many participants described as hostile school spaces. First, participants described working with/in spatialized relations that were explicitly prohibitive, racialized, and/or exclusionary. Second, I sketch the blurry boundaries of relations that resulted from efforts to (re)make, negotiate, and improve such hostile spaces. Third, I outline a set of instances when teachers refused normative spatial practices and purposely sought to create hostile spaces. The findings highlight, or at least (un/re)blur, the localized and interdependent racial/spatial relations, knowledges, and discourses that simultaneously limit and reveal the potentiality for different relations. I suggest that in mapping the shifting, contingent, and fluid spaces of Latinx teachers in South Carolina we can identify a variety of entry points to challenge the spatialized and racialized practices of power that (re)produce exclusion and marginality while also highlighting the ingenuity and creativity of teachers' own spatial interventions.